CONSTITUTIONAL AND LEGAL PRINCIPLES OF THE ORGANIZATION AND ACTIVITIES OF THE COMMITTEES OF THE Verkhovna Rada of Ukraine - Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Review of the monograph Zozuli O.I. "The constitutional and legal status of parliamentary committees in Ukraine"